Antibiotic susceptibility screening of primate-associated Clostridium ventriculi. (June 2021) - Makovska, Marie; Modrackova, Nikol; Bolechova, Petra; Drnkova, Barbora; Neuzil-Bunesova, Vera
Abstract: Clostridium ventriculi (syn. Sarcina ventriculi ) is a Gram-positive opportunistic pathogen with sarcina morphology. In the case of gastrointestinal disorders, the treatment is often empirical. Due to the common occurrence in primates and the potential risk of dysbiosis; the antibiotic susceptibility screening of C. ventriculi strains isolated from guenon monkeys and crested gibbons to 58 antibiotics was performed to reduce potentially ineffective antibiotic use in case of disease. Isolates were found to be susceptible to the majority of the tested antibiotics, mainly to (fluoro)quinolones, macrolides, penicillins, and tetracyclines. The susceptibility profiles were similar despite the hosts. Tested strains showed also natural resistance to a few antibiotics on the genus level. Detected in vitro antibiotic efficiency is consistent with documented human treatment cases. Graphical abstract: Image 1 Highlights: Detection of Clostridium ventriculi is often associated with different pathologies of the gastrointestinal tract. C. ventriculi seems to be a common bacterial taxon of primates without obvious health problems. Primate isolates were susceptible to most tested antibiotics. Commonly used human treatment with ciprofloxacin and metronidazole is also effective in vitro against the primate strains.